The AP-1 transcription factor Fosl-2 drives cardiac fibrosis and arrhythmias under immunofibrotic conditions - Stellato, Mara; Dewenter, Matthias; Rudnik, Michal; Hukara, Amela; Özsoy, Çagla; Renoux, Florian; Pachera, Elena; Gantenbein, Felix; Seebeck, Petra; Uhtjaerv, Siim; Osto, Elena; Razansky, Daniel; et al. (Communications biology, 2023)
Fibrotic changes in the myocardium and cardiac arrhythmias represent fatal complications in systemic sclerosis (SSc), however the underlying mechanisms remain elusive. Mice overexpressing transcription factor Fosl-2 (Fosl-2tg) represent animal model of SSc. Fosl-2tg mice showed interstitial cardiac fibrosis, disorganized connexin-43/40 in intercalated discs and deregulated expression of genes controlling conduction system, and developed higher heart rate (HR), prolonged QT intervals, arrhythmias with prevalence of premature ventricular contractions, ventricular tachycardias, II-degree atrio-ventricular blocks and reduced HR variability. Following stimulation with isoproterenol Fosl-2tg mice showed impaired HR response. In contrast to Fosl-2tg, immunodeficient Rag2−/−Fosl-2tg mice were protected from enhanced myocardial fibrosis and ECG abnormalities. Transcriptomics analysis demonstrated that Fosl-2-overexpression was responsible for profibrotic signature of cardiac fibroblasts, whereas inflammatory component in Fosl-2tg mice activated their fibrotic and arrhythmogenic phenotype. In human cardiac fibroblasts FOSL-2-overexpression enhanced myofibroblast signature under proinflammatory or profibrotic stimuli. These results demonstrate that under immunofibrotic conditions transcription factor Fosl-2 exaggerates myocardial fibrosis, arrhythmias and aberrant response to stress.
Gesehen am 22.03.2023